A novel test specimen for investigating the mixed mode I+III fracture toughness of hot mix asphalt composites – Experimental and theoretical study. (July 2016) - Aliha, M.R.M.; Bahmani, A.; Akhondi, Sh.
Abstract: Asphalt concrete pavements containing top-down cracks can be subjected to combined opening-out of plane sliding (i.e. mixed mode I/III) deformations due to traffic loads. However, lack of a suitable laboratory test specimen for fracture toughness testing of asphalt composites under mixed mode I/III, is one of the main shortcomings of this field. Hence, a new and simple test configuration is proposed in this research for determining mixed mode I/III fracture toughness of these composite materials. The specimen which is called the Edge Notched Disc Bend (ENDB), is a disc containing an edge crack created through one side of specimen along the diameter and is loaded by a three-point bend fixture. It was demonstrated that the complete range of mode mixity from pure mode I to pure mode III can be achieved by this specimen simply by changing the crack inclination angle relative to the loading support direction. The practical ability of the suggested ENDB specimen, was then examined for obtaining the mixed mode I/III fracture toughness of a typical hot mix asphalt (HMA) composite for different mode mixities including pure modes I and III. Corresponding values of K Ic and K IIIc were determined for each mode mixity and it is shown that the obtained results are in quite well agreement with the predictions of a mixed mode I/III fracture theory. Consequently, the ENDB specimen can be used as a favorite candidate specimen for mixed mode fracture toughness study of asphalt concrete materials.